Biomimetic Cellulose Nanocrystals Composite Hydrogels: Recent Progress in Surface Modification and Smart Soft Actuator Applications - Yuzhu Cui; Zekai Wang; Mingliang Zhao; Zhihui Wang; Lu Zong (Nanomaterials, 2025)
Cellulose nanocrystals (CNCs), derived from renewable biomass, have emerged as a pivotal component in the design of biomimetic composite hydrogels due to their exceptional mechanical strength, biocompatibility, and tunable surface chemistry. This review comprehensively explores recent advancements in surface modification strategies for CNCs (physical adsorption, chemical grafting, and bio-functionalization) and their impacts on the structure and properties of hydrogel networks, with particular emphasis on mechanical properties. Future applications in light/thermal/electrical-responsive soft actuators are critically analyzed. Guided by biomimetic design principles, the anisotropic mechanical responses induced by CNC-oriented alignment are explored, along with their cutting-edge advancements in soft robotics, wearable sensing, and biomedical devices. Perspectives are provided on future directions, including multi-stimuli synergistic actuation systems and sensing-actuation integration architectures. This work establishes a fundamental framework for designing CNC-enhanced smart hydrogels with tailored functionalities and hierarchical structures.